Phylogeny, biogeography and diversification of the mining bee family Andrenidae. (21st December 2021) - Bossert, Silas; Wood, Thomas J.; Patiny, Sébastien; Michez, Denis; Almeida, Eduardo A. B.; Minckley, Robert L.; Packer, Laurence; Neff, John L.; Copeland, Robert S.; Straka, Jakub; Pauly, Alain; Griswold, Terry; et al.
Abstract: The mining bees (Andrenidae) are a major bee family of over 3000 described species with a nearly global distribution. They are a particularly significant component of northern temperate ecosystems and are critical pollinators in natural and agricultural settings. Despite their ecological and evolutionary significance, our knowledge of the evolutionary history of Andrenidae is sparse and insufficient to characterize their spatiotemporal origin and phylogenetic relationships. This limits our ability to understand the diversification dynamics that led to the second most species‐rich genus of all bees, Andrena Fabricius, and the most species‐rich North American genus, Perdita Smith. Here, we develop a comprehensive genomic dataset of 195 species of Andrenidae, including all major lineages, to illuminate the evolutionary history of the family. Using fossil‐informed divergence time estimates, we characterize macroevolutionary dynamics, incorporate paleoclimatic information, and present our findings in the context of diversification rate estimates for all other bee tribes. We found that diversification rates of Andrenidae steeply increased over the past 15 million years, particularly in the genera Andrena and Perdita . This suggests that these two groups and the brood parasites of the genus Nomada Scopoli (Apidae), which are the primary cleptoparasitic counterparts of Andrena, are similar in age and represent the fastest diversifying lineages of all bees. Using our newly developed time frame of andrenid evolution, we estimate a late Cretaceous origin in South America for the family and reconstruct the past dispersal events that led to its present‐day distribution. Abstract : First comprehensive phylogenomic framework for the mining bee family Andrenidae. Andrenidae originated in the late Cretaceous, most likely in the Neotropical realm. Andrena and Perdita are among the most rapidly diversifying lineages of all bees.